Transdermal optogenetic peripheral nerve stimulation. (14th March 2017) - Maimon, Benjamin E; Zorzos, Anthony N; Bendell, Rhys; Harding, Alexander; Fahmi, Mina; Srinivasan, Shriya; Calvaresi, Peter; Herr, Hugh M
Abstract: Objective: A fundamental limitation in both the scientific utility and clinical translation of peripheral nerve optogenetic technologies is the optical inaccessibility of the target nerve due to the significant scattering and absorption of light in biological tissues. To date, illuminating deep nerve targets has required implantable optical sources, including fiber-optic and LED-based systems, both of which have significant drawbacks. Approach: Here we report an alternative approach involving transdermal illumination. Utilizing an intramuscular injection of ultra-high concentration AAV6-hSyn-ChR2-EYFP in rats. Main results: We demonstrate transdermal stimulation of motor nerves at 4.4 mm and 1.9 mm depth with an incident laser power of 160 mW and 10 mW, respectively. Furthermore, we employ this technique to accurately control ankle position by modulating laser power or position on the skin surface. Significance: These results have the potential to enable future scientific optogenetic studies of pathologies implicated in the peripheral nervous system for awake, freely-moving animals, as well as a basis for future clinical studies.